Dielectric properties of N-SmC* liquid crystalline composite - Yilmaz Canli, N.; Yakuphanoğlu, Fahrettin; Yasa, O.; Bilgin-Eran, B. (National Institute of Optoelectronics, 2010)
The dielectric relaxation and anisotropy properties of 4-cyano-4'-pentylbiphenyl and salicylaldimine compound (LC1) liquid crystals have been investigated. The polarizing microscopy and differential scanning calorimetry results show that the chiral salicylaldimine compound (LC1) exhibits enantiotropic SmC* mesophases. The dielectric anisotropy of the liquid crystals changes from positive type to negative type. The critical frequency values of dielectrical anisotropy for 4-cyano-4'-pentylbiphenyl and salicylaldimine compound (LC1) were found to be 693.84 and 577.61 kHz, respectively. The dielectric anisotropy value of 5CB/LC1 liquid crystal composite is lower than 5CB liquid crystal. It is evaluated that the 5CB/LC1 composite liquid crystal gives new dielectrical anisotropy and electrical properties.
Keywords: Dielectric anisotropy; Electrical properties; Liquid crystal